India and Southeast Asia - "Ayoob, Mohammed" (London, 1990)
This title, first published in 1990, provides a close contextual analysis of how influential Indian policy-makers have perceived India's interests within the ASEAN region since Indian independence in 1947. Placing these perceptions in the context of India's broad strategic and foreign policy framework, Ayoob analyses the policies which had emerged by the close of the 1980s and stresses the close link between the futures of the two regions. Including a thorough analysis of superpower involvement, as well as Indian relations with Indonesia, Vietnam and Cambodia, this is a comprehensive study of great value to students with an interest in Indian and Southeast Asian history and diplomacy.
Keywords: "Asia, Southeastern - Foreign relations - India"